Facile Oximation of Carbonyl Compounds with Titanyl Acetylacetonate/NH2OH System - ZEYNIZADEH, BEHZAD; AMJADI, ELNAZ (Asian Journal of Chemistry, 2010)
Structurally different aldehydes and ketones were efficiently converted to their corresponding oximes by TiO(acac)2/NH2OH·HCl system. The reactions were carried out in refluxing CH3CN to give the products in high to excellent yields.